Biosynthetic infochemical communication. (10th July 2015) - Olsson, S B; Challiss, R A J; Cole, M; Gardeniers, J G E; Gardner, J W; Guerrero, A; Hansson, B S; Pearce, T C
Abstract: There is an ever-increasing demand for data to be embedded in our environment at ever-decreasing temporal and spatial scales. Whilst current communication and storage technologies generally exploit the electromagnetic properties of media, chemistry offers us a new alternative for nanoscale signaling using molecules as messengers with high information content. Biological systems effectively overcome the challenges of chemical communication using highly specific biosynthetic pathways for signal generation together with specialized protein receptors and nervous systems. Here we consider a new approach for information transmission based upon nature's quintessential example of infochemical communication, the moth pheromone system. To approach the sensitivity, specificity and versatility of infochemical communication seen in nature, we describe an array of biologically-inspired technologies for the production, transmission, detection, and processing of molecular signals. We show how it is possible to implement each step of the moth pheromone pathway for biosynthesis, transmission, receptor protein binding/transduction, and antennal lobe processing of monomolecular and multimolecular signals. For each implemented step, we discuss the value, current limitations, and challenges for the future development and integration of infochemical communication technologies. Together, these building blocks provide a starting point for future technologies that can utilize programmable emission and detection of multimolecular information for a new and robust means of communicating chemical information.